(untitled) (Innovative professional education, 2022)
The main approaches to quality assessment of dissertation research are highlighted. Based on the generalization of the positions of scientists regarding the evaluation of the theoretical and methodological significance of the dissertation, the technology of operationalanalysis of the quality of scientific and pedagogical research is proposed as a seven-stage diagnostic algorithm. The technology of operational analysis is presented, according to which the reviewer of the dissertation (or, in fact, its author), analyzing the logical connections "research topic – goal", "research goal – task", "research task – subdivisions of the dissertation", "subdivisions – scientific results ", "scientific results – published works", "scientific results – novelty", "research task – conclusions" can form an idea about the methodological integrity of the dissertation work based on the indicated indicators, quickly assess its quality and make a scientifically balanced and responsible decision regarding the prospects of its defense.